Composito de poliuretano de mamona e residuo industrial para isolacao termica e absorcao sonora - Oliveira, Maria Cleide Ribeiro de (2010)
This work proposes the development of an innovative material made from a vegetable polyurethane matrix and load of industrial waste, from retread tires, for thermal insulation and environmental comfort. Experimental procedures are presented, as well as the results of the thermal and acoustic performance of this composite material, made from an expansive foam derived from the castor seed oil and fiber of scrap tires. The residue was treated superficially with sodium hydroxide, to eliminate contaminants, and characterized macroscopically and microscopically. Samples were produced with addition of residues at levels of 5%, 10%, 15% and 20% by weight, for determination of thermal properties: conductivity, heat capacity and thermal diffusivity, sound absortion index and density. The results were compared to commercially available thermal insulation and sound absorbing products. According to the analysis of results, it was concluded that the developed composite presents characteristics that qualify it as a thermal insulation with superior performance, compared to commercial available insulation, and sound absorption capacity greater than the castor oil polyurethane s, without addition of the residue